2020
DOI: 10.3892/mmr.2020.11580
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle‑mediated delivery of paclitaxel and nucleic acids for cancer therapy (Review)

Abstract: Paclitaxel is a potent antineoplastic agent, but poor solubility and resistance have limited its use. Gold nanoparticles (aunPs) are widely studied as drug carriers because they can be engineered to prevent drug insolubility, carry nucleic acid payloads for gene therapy, target specific tumor cell lines, modulate drug release and amplify photothermal therapy. consequently, the conjugation of paclitaxel with aunPs to improve antiproliferative and pro-apoptotic potency may enable improved clinical outcomes. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…To form novel NDC-1 and NDC-2 drug conjugate gold nanoparticles, thiol-Au covalent bonds were used and then their solubility, stability, and anti-cancer efficacy were evaluated. Previously, AuNPs have been effectively used for drug dispersity in the literature. Zhang et al attached Paclitaxel to AuNPs via DNA linkers for increased solubility and effectiveness . In another study, Paclitaxel was attached to AuNPs through thiol-terminated polyethylene glycol molecules and enhanced performance was obtained due to higher solubility and stability .…”
Section: Resultsmentioning
confidence: 99%
“…To form novel NDC-1 and NDC-2 drug conjugate gold nanoparticles, thiol-Au covalent bonds were used and then their solubility, stability, and anti-cancer efficacy were evaluated. Previously, AuNPs have been effectively used for drug dispersity in the literature. Zhang et al attached Paclitaxel to AuNPs via DNA linkers for increased solubility and effectiveness . In another study, Paclitaxel was attached to AuNPs through thiol-terminated polyethylene glycol molecules and enhanced performance was obtained due to higher solubility and stability .…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the molecular targets of Cu@Fe NPs do not overlap with those of conventional antibiotics, based on the properties of NPs, if antibiotics are adsorbed on the surface of nanocarriers, the synergistic effect of both nanoparticles can improve the ability of loaded drugs to pass through cell membranes and the uptake of antibiotics, which ultimately leads to an increase in antibacterial activity ( Azzopardi et al, 2013 ; Wong et al, 2013 ; Jelinkova et al, 2019 ). It has been reported that NPs as drug carriers can effectively load the first-line chemotherapeutic drug paclitaxel and improve the chemotherapeutic efficacy of paclitaxel in the treatment of cancers such as ovarian cancer ( Wang et al, 2020 ; Wu et al, 2021 ). Therefore, Cu@Fe NPs in combination with antibiotic therapy is also a new avenue to be considered, which awaits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, spherical Au nanoparticles have been attracting considerable interest as non-toxic drug carrier systems for cancer treatment, thanks to the large surface-to-volume ratio; easy tuning of surface charge, hydrophilicity, and functionality; and outstanding stability [ 37 , 38 , 39 ]. Various biocompatible polymers (e.g., polyethylene glycol (PEG) [ 40 ], polyelectrolyte [ 37 ], DNA [ 25 ], liposome [ 41 ], and other bio-macromolecules [ 42 ]) can be used to tune the tumor microenvironment [ 43 ] and, more importantly, enhance the stability, payload capacity, and the cellular uptake.…”
Section: Gold Nanostructures For Cancer Treatmentmentioning
confidence: 99%